2017
DOI: 10.1002/jcb.26385
|View full text |Cite
|
Sign up to set email alerts
|

FGFR2 regulation by picrasidine Q inhibits the cell growth and induces apoptosis in esophageal squamous cell carcinoma

Abstract: Fibroblast growth factor receptor (FGFR) 2 and its downstream signaling cascades, PI3 K/AKT/mTOR is playing an important role in cell survival and proliferations. In this study, we firstly found that picrasidine Q (PQ), an alkaloid component extracted from Angelica keiskei species, has the capacity of anti-cell transformation and anti-cancer. After ligand shape similarity approach of PQ, we found that PQ targeted FGFR 2 and verified by FGFR2 kinase assay as well as computational docking model. FGFR2 highly exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
(81 reference statements)
0
14
0
Order By: Relevance
“…For their bioactivities, C11 was reported as a TMV inhibitor (Chen et al, 2009a) and C12 (KOIKE and OHMOTO, 1986) showed none of anti-inflammatory effects and cytotoxicity against RAW 264.7 cells (Liu P. et al, 2019), while C13 had good cytotoxicity against the human cervical HeLa cell line, with an IC 50 value around 20 μM (Guo et al, 2020). C14 has antihepatoma potential l (Zhao et al, 2019d), and C15 exhibited anti-inflammatory activity (Liu P. et al, 2019) and cytotoxicity against RAW 264.7 (Liu P. et al, 2019), esophageal squamous carcinoma cells (Shi et al, 2018), and also beneficial effects in cerebral protection (Sasaki et al, 2016). From the literatures, C16, C19, C20, and C21 had cytotoxicity against human cervical HeLa, gastric MKN-28 cancer, and mouse melanoma B-16 cancer cells (Jiao et al, 2015), and C21 also strongly inhibited osteoclast formation (Kong et al, 2017).…”
Section: Bioactivity Discussion Of Kumu Compoundsmentioning
confidence: 99%
“…For their bioactivities, C11 was reported as a TMV inhibitor (Chen et al, 2009a) and C12 (KOIKE and OHMOTO, 1986) showed none of anti-inflammatory effects and cytotoxicity against RAW 264.7 cells (Liu P. et al, 2019), while C13 had good cytotoxicity against the human cervical HeLa cell line, with an IC 50 value around 20 μM (Guo et al, 2020). C14 has antihepatoma potential l (Zhao et al, 2019d), and C15 exhibited anti-inflammatory activity (Liu P. et al, 2019) and cytotoxicity against RAW 264.7 (Liu P. et al, 2019), esophageal squamous carcinoma cells (Shi et al, 2018), and also beneficial effects in cerebral protection (Sasaki et al, 2016). From the literatures, C16, C19, C20, and C21 had cytotoxicity against human cervical HeLa, gastric MKN-28 cancer, and mouse melanoma B-16 cancer cells (Jiao et al, 2015), and C21 also strongly inhibited osteoclast formation (Kong et al, 2017).…”
Section: Bioactivity Discussion Of Kumu Compoundsmentioning
confidence: 99%
“…Although a number of FDA approved therapies, such as growth factor receptor inhibitors and immunotherapies are currently used in clinical settings, none of these therapies are uniformly effective in all patient groups. Thus the hunt for novel therapies remains a constant venture to the research scientists (Shi et al, 2018;Song et al, 2018Song et al, , 2019Xu et al, 2018;Ji et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The cell cycle and apoptosis were detected as previously described ( Shi et al, 2018 ). Cells were cultured and treated with DMSO and HF (0.05 and 0.2 μM) in both NCI-H460 and NCI-H1299 for 24 h, followed by single staining with PI (Beyotime) for cell cycle analysis and double staining with PI and Annexin V-FITC (Beyotime) for apoptosis analysis.…”
Section: Methodsmentioning
confidence: 99%